Preparation of a nontraditional ultralight fluid for increasing oil production using natural, ground, and acid-activated clay - Munawar, K.; Badrul, M.J.; Abdul Raman, Abdul Aziz (2011)
The effect of previously treated and natural clay on the rheological properties of an ultralight drill-in fluid was investigated. The clay was used as a disperser to create a stable, low-density drilling mud. The clay was treated by grinding and acid activation. The effect of incorporating different types of clay in the fluid was determined by Fourier-transform infrared spectroscopy (IR), x-ray diffraction analysis, x-ray spectral fluorescence analysis, electron scanning microscopy, and granulometric particle analysis. It was shown that in contrast to treated clay, on addition of untreated clay, the stability of the fluid increased significantly. Â© 2011 Springer Science+Business Media, Inc.